EFFECT OF AERATION AND RECIRCULATION IN THE REMOVAL OF NITROGEN AND CHEMICAL OXYGEN DEMAND FROM SANITARY SEWAGE IN A STRUCTURED BED REACTOR - Leick,Sheilla A. (2017)
ABSTRACT This study aimed to evaluate a structured bed reactor with intermittent aeration in the simultaneous removal of Chemical Oxygen Demand (COD) and Total Nitrogen (TN) from sanitary sewage. The reactor was operated for 339 days with a Hydraulic Retention Time (HRT) of 12 hours, temperature of 30 ± 1°C and continuous feeding. Nine trials were carried out in which three different effluent recirculation flow (Qr), 3, 2 and 1 time the incoming flow, were evaluated in three different aeration times, of 1h, 2h, and 3h, in 3 hour cycles. The results showed that different recirculation flows and aeration times did not influence the removal of COD, which reached 89%±12. It was observed that the efficiency of TN removal was higher in the tests with higher COD/TKN ratio, between 7.2 and 7.8, reaching TN effluent values of 17 mg.L-1, being 5 mg.L-1 of N-NH4+, 2 mg.L-1 of N-NO2 and 10 mg.L-1 of N-NO3-. It was verified that it is possible to remove the COD and nitrogen from sanitary sewage in a structured bed reactor with intermittent aeration.